Estágio supervisionado em construtora especializada em obras públicas - Silva, Erli Gomes da (Brasil, 2023)
The report describes the internship period of a civil engineering student at a construction company specializing in public works. The main activities reported are linked to budgeting and monitoring of contracts and works using measurement spreadsheets. It is presented how the student's first professional experience and his daily business experience impacted his view of the importance of engineering professionals and what awaits them in the job market.